Case report: Five-year periodontal management of a patient with two novel mutation sites in ELANE-induced cyclic neutropenia - Lao, Zhentao; Fu, Jiarun; Wu, Zhiying; Zhu, Lihong; Wu, Shiwen; Lin, Yongheng; Hu, Chaoming; Duan, Dingyu; Wang, Panpan (Frontiers in Genetics, 2022)
Cyclic Neutropenia (CyN) is a rare, ELANE-related neutropenia. As one of the initial manifestations of CyN, oral manifestation is an important reason that brings patients to professional help. This case report describes a 12-year-old girl with recurrent oral ulcers, severe chronic periodontitis, and pathological tooth migration as initial and main clinical symptoms of CyN. Two novel mutations in the ELANE gene, c.180T>G (p.I60M) and c.182C>G (p.A61G), were reported in CyN for the first time. Bioinformatic research indicates lower stability and impaired molecular linkages of mutant neutrophil elastase (NE) encoded by ELANE. However, there was no substantial change in enzyme affinity to the classic substrate Suc-Ala-Ala-Ala-pNA, suggesting that the impaired integrity and stability of the mutant NE, rather than catalytic deficiency, may be the pathogenic mechanism of ELANE mutation-induced neutropenia. The patient was prescribed scaling and root planing (SRP) and monthly periodontal maintenance without systemic management. Although the routine periodontal treatment was interrupted by the 2019 Coronavirus pandemic occasionally, the patient’s periodontal devastation was still well remitted after a 5-year follow-up. This study confirmed the importance of plaque control and proper diagnosis in the periodontal management of such patients and aimed to provide better clinical references. In addition, the novel mutations found in this study expand the spectrum of known mutations of the ELANE gene in CyN and further contribute to its pathogenic mechanism.